Evaluating the Malay version of NIOSH WellBQ: a study on reliability and construct validity for enhanced workplace well-being assessment - Omar, Aswandi; Guan, Ng Yee; Nair Mohan, Sindhu; Mokhtar, Siti Aisah; Poh Ying, Lim (F1000 Research Ltd, 2024)
This study aimed to validate the Worker Well-Being Questionnaire, originally developed by the US National Institute for Occupational Safety and Health, in the Malay language. The translation process involved an initial independent translation by a professional translator, followed by a comparison of translations to synthesize a unified version, which was subsequently back-translated. The backtranslations were then reviewed by an expert committee to create a finalized questionnaire version. The results of this validation study indicate a high level of satisfaction, demonstrating an excellent fit with confirmatory factor analysis (CFI and TLI values ranging from 0.96 to 0.99) and a low root mean square error of approximation (RMSEA values ranging from 0.03 to 0.07). Moreover, the questionnaire exhibits sound internal consistency, with Cronbach’s alpha values exceeding 0.7, and the factor structures align with theoretical expectations. In conclusion, the Malay version of the questionnaire faithfully reproduces the original instrument, enabling a robust and efficient assessment of workers’ well.